High-voltage-withstanding integrally-formed inductor and preparation method thereof

By using iron-based nanocrystals and composite powder in the inductor, and combining resin mixture, the problem of alloy inductors heat and short circuit under large currents is solved, and higher voltage resistance and stability are achieved, and losses are reduced. .

CN119153208AInactive Publication Date: 2024-12-17SHENZHEN BEST ELECTRONICS CO LTD

Patent Information

Application Number
CN202411649451.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing alloy-type integrated inductor heats up due to the large induced current under large currents, resulting in damage to the resin insulation layer, which in turn causes short circuits of the windings and magnets in the inductor, increase product losses, and poor voltage impact resistance.

Method used

Magnets are prepared using iron-based nanocrystals and composite powders. By controlling the content and particle size of copper and manganese, the phosphating layer and alumina or silicon oxide coating are added, and the resin mixture is combined to improve resistivity and magnetic properties and reduce hysteresis loss. , enhance pressure resistance.

Benefits of technology

It effectively improves the inductor's voltage impact resistance and stability, reduces product losses, extends service life, reduces windings and magnets short circuits, and improves product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a high-voltage-withstanding integrally-formed inductor and a preparation method thereof.The high-voltage-withstanding integrally-formed inductor comprises a magnet and a winding, the magnet is prepared from iron-based nanocrystalline and composite powder, and the iron-based nanocrystalline comprises, by weight, 10-15% of cobalt, 7-15% of nickel, 1-3.5% of manganese, 3-6% of silicon, 0.3-1% of copper and the balance iron; the composite powder comprises any one or a mixture of more of carbonyl iron, iron-silicon-chromium and iron-silicon-aluminum. The method has the effect of improving the quality of an inductor product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic equipment technology, and in particular to a high-voltage integrally formed inductor and a preparation method thereof. Background Art

[0002] With the development of automotive electronics, the number of functional modules in automobiles has increased, and inductors are widely used as one of the core components for voltage conversion.

[0003] Since the power of inductor devices is relatively large, alloy-based integrated inductors are more commonly used. However, alloy-based integrated inductors currently have poor voltage shock resistance due to the low resistivity of metal materials. Under large currents, they generate heat due to the large induced current, causing damage to the resin insulation layer, and further causing short circuits in the windings and magnets within the inductor, which in turn leads to increased product losses. Summary of the invention

[0004] In order to solve the above problems, the present application provides a high-voltage integrally formed inductor and a preparation method thereof.

[0005] The present application provides a high-voltage integrally formed inductor and a preparation method thereof using the following technical solutions: In a first aspect, the present application provides a high-voltage integrally formed inductor, which adopts the following technical solution: A high-voltage integrally formed inductor comprises a magnet and a winding, wherein the magnet is prepared from iron-based nanocrystals and composite powder, and the iron-based nanocrystals comprise the following components in parts by weight: Cobalt 10-15wt%, nickel 7-15wt%, manganese 1-3.5wt%, silicon 3-6wt%, copper 0.3-1wt%, and the balance is iron; the composite powder comprises any one or more of carbonyl iron, iron silicon chromium and iron silicon aluminum.

[0006] By adopting the above technical solution, the ratio of magnetic materials is limited, and the grain size of nanocrystals of the iron-cobalt alloy and iron-nickel alloy composite structure is controlled by the content of copper and manganese, which can reduce the hysteresis loss of the material, so that the resistivity is improved and the pressure impact resistance is further improved. Iron-based nanocrystals are added to the system. Iron-based nanocrystals have excellent comprehensive magnetic properties, such as high saturation magnetic induction, high initial magnetic permeability, low product loss, etc., which promote the performance improvement of the inductor and can further improve the stability of the inductor.

[0007] Preferably, the particle size of the iron-based nanocrystals is 12-53 um; the particle size of the composite powder is 3-8 um.

[0008] By adopting the above technical solution, preferably the particle size of the iron-based nanocrystals is within the above range, and preferably the particle size of the composite powder is within the above range, the stability of the prepared magnet can be further improved.

[0009] Preferably, the surface of the iron-based nanocrystal contains a phosphating layer, and the thickness of the phosphating layer is 10-20 nm.

[0010] By adopting the above technical solution, a phosphating layer is added to the surface of the iron-based nanocrystals, and the magnetic layer is thickened, so that the magnetic field of the prepared magnet is improved, and the resistivity of the prepared magnet is increased, while the magnetic loss is improved, thereby improving the product quality of the prepared inductor and effectively reducing product loss. The thickness of the phosphating layer is limited, which can further improve the stability of the prepared iron-based nanocrystals.

[0011] Preferably, the surface of the composite powder contains a coating layer, the coating layer is one of aluminum oxide or silicon oxide, and the thickness of the coating layer is 5-10 nm.

[0012] By adopting the above technical solution, adding an aluminum oxide or silicon oxide coating layer on the surface of the composite powder can further increase the density of the magnetic material, thereby further improving the stability of the prepared magnet and playing a role in regulating the magnetism, thereby further improving the quality of the prepared inductor product. At the same time, the thickness of the coating layer is preferably 5-10nm, which can further improve the stability of the prepared magnet.

[0013] Preferably, the iron-based nanocrystals account for 35-55wt% of the magnet.

[0014] By adopting the above technical solution, preferably the content of iron-based nanocrystals is within the above range, which can further improve the stability of the prepared magnet.

[0015] Preferably, the magnet also includes a resin mixture, which accounts for 1.0-2.5wt% of the magnet. The resin mixture includes a resin matrix and an insulating composite, the resin matrix includes a mixture of any one or more of epoxy resin, phenolic resin, polyester resin and silicone resin, and the insulating composite includes a mixture of any one or more of aluminum nitride, boron nitride and silicon nitride.

[0016] By adopting the above technical solution, the resin mixture contains an insulating composite, which can reduce the problem of local excessive temperature in the alloy material in the system, thereby improving the stability and service life of the inductor during operation, improving the pressure resistance of the product during operation, reducing the phenomenon of winding and magnet short circuit in the product during operation, and reducing product losses.

[0017] Preferably, the insulating composite accounts for 10-15wt% of the resin mixture.

[0018] By adopting the above technical solution, the content of the insulating composite in the mixed resin is preferably within the above range, which can further improve the stability of the prepared resin mixture.

[0019] Preferably, the particle size of the insulating composite particles is 18-40 nm.

[0020] By adopting the above technical solution, the particle size of the insulating composite is preferably within the above range, which can further improve the comprehensive performance of the prepared resin mixture.

[0021] In a second aspect, the present application provides a method for preparing a high-voltage integrally formed inductor, which adopts the following technical solution: Preferably, a method for preparing a high-voltage integrally formed inductor comprises the following steps: An insulating layer structure is made outside the magnet, and then the winding is wound on the middle column of the magnet, and then positioned inside the magnet by hot pressing. At the same time, the bottom of the magnet is fixed by motor welding to form an external electrode to complete the inductance preparation.

[0022] In summary, the present application includes at least one of the following beneficial technical effects: In the present application, the proportion of the magnet material is designed, and the grain size of the nanocrystals of the highly saturated iron-cobalt alloy and iron-nickel alloy composite structure is controlled by the content of copper and manganese, so that the hysteresis loss of the material can be reduced, so that the resistivity of the prepared magnet is further improved. Iron-based nanocrystals are also added to the magnet. The iron-based nanocrystals have excellent comprehensive magnetic properties, can further improve the magnetic induction and initial magnetic permeability of the inductor, and reduce product losses, so as to further improve product quality. The surface of the iron-based nanocrystal contains a phosphating layer, and the thickness of the phosphating layer is specifically defined, so that the thickness of the magnetic layer can be increased, thereby effectively improving the magnetic field of the prepared magnet, and at the same time improving the resistivity of the prepared magnet, so that the magnetic loss is further improved, so as to improve the product quality of the prepared inductor, and effectively reduce the product loss, and improve the stability of the prepared iron-based nanocrystal. At the same time, a coating layer of aluminum oxide or silicon oxide is added to the surface of the composite powder to further improve the density of the magnetic material, and synergistically improve the stability of the magnet with the iron-based nanocrystal, so that the product quality is further improved; There is also a resin mixture in the magnet. The insulating composite in the resin mixture is composed of insulating materials with excellent thermal conductivity such as aluminum nitride, boron nitride and silicon nitride. It can reduce the problem of local excessive temperature in the alloy material in the system, thereby improving the stability and service life of the inductor during operation, and then improving the product's pressure resistance during operation, so as to reduce the phenomenon of winding and magnet short circuit in the product during operation, and further reduce product losses. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Example 1

[0024] The iron-based nanocrystalline powder, composite powder and resin mixture powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours and then cooled to obtain a magnet.

[0025] The winding is wound on the middle column of the magnet, and is hot-pressed to the inside of the magnet at a temperature of 180°C, a pressure of 150MPa, and a time of 30s. The winding is fixed by electrode welding to form an external electrode, and an integrally formed inductor is prepared.

[0026] The resin mixture powder accounts for 2.5wt%, the composite powder accounts for 45wt%, and the rest is iron-based nanocrystalline powder; the composition of the iron-based nanocrystalline powder is 10wt% cobalt, 7wt% nickel, 1wt% manganese, 3wt% silicon, 0.3wt% copper, and the rest is iron; the particle size of the iron-based nanocrystalline is 12-53um, and the surface of the iron-based nanocrystalline contains a phosphide layer with a thickness of 10-20nm; the composite powder is sendustine powder, the particle size of the sendustine powder is 3-8um, and the surface of the sendustine powder contains a 5-10nm coating layer, and the coating layer is aluminum oxide; the resin mixture powder includes a resin matrix and an insulating composite, and the resin matrix is ​​prepared by mixing epoxy resin, phenolic resin and silicone resin, wherein epoxy resin accounts for 45wt% of the resin matrix, phenolic resin accounts for 43wt% of the resin matrix, and the rest is silicone resin; the insulating composite is silicon nitride particles with a particle size of 18-40nm, and the insulating composite is 10% of the mass of the resin matrix. Example 2

[0027] The iron-based nanocrystalline powder, composite powder and resin mixture powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours and then cooled to obtain a magnet.

[0028] The winding is wound on the middle column of the magnet, and is hot-pressed to the inside of the magnet at a temperature of 180°C, a pressure of 150MPa, and a time of 30s. The winding is fixed by electrode welding to form an external electrode, and an integrally formed inductor is prepared.

[0029] The resin mixture powder accounts for 1.5wt%, the composite powder accounts for 55wt%, and the rest is iron-based nanocrystalline powder; the composition of the iron-based nanocrystalline powder is 12.5wt% cobalt, 13wt% nickel, 2.5wt% manganese, 5.0wt% silicon, 0.6wt% copper, and the rest is iron; the particle size of the iron-based nanocrystalline is 12-53um, and the surface of the iron-based nanocrystalline contains a phosphide layer with a thickness of 10-20nm; the composite powder is prepared by mixing iron silicon aluminum powder, carbonyl iron powder and iron silicon chromium powder in a mass ratio of 1:1:1 The obtained iron silicon chromium powder has a particle size of 3-8um, and the surface of the composite powder contains a coating layer of 5-10nm, which is silicon oxide; the resin mixture powder includes a resin matrix and an insulating composite, and the resin matrix is ​​prepared by mixing epoxy resin, polyester resin and silicone resin, wherein the epoxy resin accounts for 52wt% of the resin matrix, the polyester resin accounts for 35wt% of the resin matrix, and the rest is silicone resin; the insulating composite is boron nitride particles with a particle size of 18-40nm, and the insulating composite accounts for 12% of the mass of the resin matrix. Example 3

[0030] The iron-based nanocrystalline powder, composite powder and resin composite powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours and then cooled to obtain a magnet.

[0031] The winding is wound on the middle column of the magnet, positioned inside the magnet at a hot pressing temperature of 120° C., and fixed by electrode welding to form an external electrode to prepare an integrated inductor.

[0032] The resin mixture powder accounts for 1.0wt%, the composite powder accounts for 65wt%, and the rest is iron-based nanocrystalline powder; the composition of the iron-based nanocrystalline powder is 15wt% cobalt, 15wt% nickel, 3.5wt% manganese, 6wt% silicon, 1wt% copper, and the rest is iron; the particle size of the iron-based nanocrystalline is 12-53um, and the surface of the iron-based nanocrystalline contains a phosphide layer with a thickness of 10-20nm; the composite powder is carbonyl iron powder, the particle size of the carbonyl iron powder is 3-8um, and the surface of the composite powder contains a 5-10nm coating layer, and the coating layer is silicon oxide; the resin mixture powder includes a resin matrix and an insulating composite, the resin matrix is ​​prepared by mixing epoxy resin and silicone resin, wherein the epoxy resin accounts for 82wt% of the resin matrix, and the rest is silicone resin; the insulating composite is aluminum nitride particles with a particle size of 18-40nm, and the insulating composite is 15% of the mass of the resin matrix.

[0033] Comparative Example 1 The sendust powder and the resin mixture powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours, and then cooled to obtain a magnet.

[0034] The winding is wound on the middle column of the magnet, and is hot-pressed to the inside of the magnet at a temperature of 180°C, a pressure of 150MPa, and a time of 30s. The winding is fixed by electrode welding to form an external electrode, and an integrally formed inductor is prepared.

[0035] The resin mixture powder accounts for 2.5wt% and the rest is Sendust powder; the Sendust powder includes 55wt% powder with a particle size of 12-53um and 45wt% powder with a particle size of 3-8um, the surface of the Sendust powder contains a 5-10nm coating layer, and the coating layer is aluminum oxide; the resin mixture powder includes a resin matrix and an insulating composite, wherein the resin matrix is ​​prepared by mixing epoxy resin, phenolic resin and silicone resin, wherein epoxy resin accounts for 45wt% of the resin matrix, phenolic resin accounts for 43wt% of the resin matrix, and the rest is silicone resin; the insulating composite is silicon nitride with a particle size of 18-40nm, and the insulating composite is 10wt% of the mass of the resin matrix.

[0036] Comparative Example 2 The iron-based nanocrystalline powder and the resin mixture powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours, and then cooled to obtain a magnet.

[0037] The winding is wound on the middle column of the magnet, positioned inside the magnet at a hot pressing temperature of 120° C., and fixed by electrode welding to form an external electrode to prepare an integrated inductor.

[0038] The resin mixture powder accounts for 2.5wt% and the rest is iron-based nanocrystalline powder; the composition of the iron-based nanocrystalline powder is 10wt% cobalt, 7wt% nickel, 1wt% manganese, 3wt% silicon, 0.3wt% copper, and the rest is iron; the particle size of the iron-based nanocrystals is 12-53um, and the surface of the iron-based nanocrystals contains a phosphating layer with a thickness of 10-20nm; the resin mixture powder includes a resin matrix and an insulating composite, and the resin matrix is ​​prepared by mixing epoxy resin, phenolic resin and silicone resin, wherein epoxy resin accounts for 45wt% of the resin matrix, phenolic resin accounts for 43wt% of the resin matrix, and the rest is silicone resin; the insulating composite is silicon nitride particles with a particle size of 18-40nm, and the insulating composite is 10% of the mass of the resin matrix.

[0039] Comparative Example 3 The iron-based nanocrystalline powder, composite powder and resin mixture powder are pressed, sintered at 1000°C for 8 hours, tempered at 900°C for 3 hours, aged at 520°C for 4 hours and then cooled to obtain a magnet.

[0040] The winding is wound on the middle column of the magnet, positioned inside the magnet at a hot pressing temperature of 120° C., and fixed by electrode welding to form an external electrode to prepare an integrated inductor.

[0041] The resin mixture powder accounts for 2.5wt% of the magnet, the composite powder accounts for 45wt% of the magnet, and the rest is iron-based nanocrystalline powder; the composition of the iron-based nanocrystalline powder is 10wt% cobalt, 7wt% nickel, 1wt% manganese, 3wt% silicon, 0.3wt% copper, and the rest is iron; the particle size of the iron-based nanocrystalline is 12-53um, and the surface of the iron-based nanocrystalline contains a phosphating layer with a thickness of 10-20nm; the composite powder is sendustine powder, the particle size of the sendustine powder is 3-8nm, and the surface of the sendustine powder contains a 5-10nm coating layer, and the coating layer is aluminum oxide; the resin mixture powder includes a resin matrix, and the resin matrix is ​​prepared by mixing epoxy resin, phenolic resin and silicone resin, wherein the epoxy resin accounts for 50wt% of the resin matrix, the phenolic resin accounts for 48wt% of the resin matrix, and the rest is silicone resin.

[0042] Performance testing The following performance tests were performed on the samples of Examples 1-3 and Comparative Examples 1-3: The 3260B LCR tester was used to test the inductance value of the initial magnetic permeability μi (1V / 1MHz) of the magnetic ring sample; the SY8219 hysteresis loop tester was used to test the product loss Pc (2MHz / 1V); the DSM-8104 withstand voltage tester was used to test the breakdown voltage between the product coil and the magnet (leakage current 1mA); each sample of the above tests was tested three times, and the average value was taken and the test results were filled in Table 1, where the sample dimensions were all 1.4mm long * 1.2mm wide * 0.65mm high for testing.

[0043] Table 1 Test results of samples of Examples 1-3 and Comparative Examples 1-3

[0044] Data Analysis: Compared with Example 2, the proportions of the resin mixture and the composite powder in Example 1 are increased, and the content of iron-based nanocrystals is decreased. The decrease in iron-based nanocrystals leads to an increase in product loss. At the same time, the composition and proportion of the resin matrix in Example 1, as well as the composition and proportion of the insulating composite are adjusted, which affects the insulation performance of the system, and thus affects the values ​​of product loss and breakdown voltage in Example 1.

[0045] Compared with Example 2, the proportion of the resin mixture in Example 3 is decreased, the proportion of the composite powder is increased, and the component of the iron-based nanocrystals is adjusted, which has a certain impact on the product loss of the inductor. At the same time, the vertical matrix of the resin mixture in Example 3 only includes epoxy resin and silicone resin, and the material of the insulating composite is changed, which has a certain impact on the insulation performance of the system. Therefore, Example 3 has a greater impact on the numerical values ​​of the product loss and breakdown voltage.

[0046] Compared with Example 2, Comparative Example 1 does not add iron-based nanocrystals. The inductor without the addition of iron-based nanocrystals seriously affects the product loss. At the same time, the components and ratios of the resin mixture also change, which also seriously affects the insulation performance and magnetic permeability of the system. Therefore, the performance of Comparative Example 1 is significantly reduced.

[0047] Compared with Example 2, Comparative Example 2 does not add composite powder, and the components and ratios of the resin mixture are also changed, which affects the product loss and insulation performance of the inductor. Therefore, the performance of Comparative Example 2 is reduced.

[0048] Compared with Example 2, the composition of the iron-based nanocrystals in Comparative Example 3 is changed. At the same time, the resin mixture powder only contains a resin matrix without adding an insulating composite. Therefore, the product loss and insulation performance of Comparative Example 3 are affected, and the initial magnetic permeability of the product is also affected to a certain extent. Therefore, the performance of Comparative Example 3 is reduced.

[0049] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high withstand voltage integrated inductor, characterized in that: The invention comprises a magnet and a winding, wherein the magnet is prepared from iron-based nanocrystals and composite powders, and the iron-based nanocrystals comprise the following components in parts by weight: Cobalt 10-15wt%, nickel 7-15wt%, manganese 1-3.5wt%, silicon 3-6wt%, copper 0.3-1wt%, and the balance is iron; the composite powder comprises any one or more of carbonyl iron, iron silicon chromium and iron silicon aluminum.

2. The high withstand voltage integrated inductor according to claim 1, characterized in that: The particle size of the iron-based nanocrystals is 12-53 um; the particle size of the composite powder is 3-8 um.

3. The high withstand voltage integrated inductor according to claim 1, characterized in that: The surface of the iron-based nanocrystal contains a phosphating layer, and the thickness of the phosphating layer is 10-20 nm.

4. The high withstand voltage integrated inductor according to claim 1, characterized in that: The surface of the composite powder contains a coating layer, which is one of aluminum oxide and silicon oxide, and has a thickness of 5-10 nm.

5. The high withstand voltage integrated inductor according to claim 1, characterized in that: The iron-based nanocrystals account for 35-55 wt % of the magnet.

6. The high withstand voltage integrated inductor according to claim 1, characterized in that: The magnet also includes a resin mixture, which accounts for 1.0-2.5wt% of the magnet. The resin mixture includes a resin matrix and an insulating composite. The resin matrix includes any one or more of epoxy resin, phenolic resin, polyester resin and silicone resin, and the insulating composite includes any one or more of aluminum nitride, boron nitride and silicon nitride.

7. The high withstand voltage integrated inductor according to claim 6, characterized in that: The insulating composite accounts for 10-15 wt % of the resin mixture.

8. The high withstand voltage integrated inductor according to claim 7, characterized in that: The particle size of the insulating composite particles is 18-40 nm.

9. A method for preparing the high withstand voltage integrated inductor according to claim 1, characterized in that: The steps include: An insulating layer structure is made outside the magnet, and then the winding is wound on the middle column of the magnet, and then positioned inside the magnet by hot pressing. At the same time, the bottom electrode of the magnet is welded and fixed to form an external electrode to complete the inductance preparation.

Citation Information

Patent Citations

  • Method for improving coercivity of Nd-Fe-B magnet

    CN106601407A

  • Iron-based amorphous and nanocrystalline magnetically soft alloy powder, nanocrystalline magnetic powder core and application of iron-based amorphous and nanocrystalline magnetically soft alloy powder and nanocrystalline magnetic powder core

    CN117153515A

  • Drop-resistant low-alternating-current-resistance integrally-formed inductance material and preparation method thereof

    CN117912807A

  • Nanocrystalline magnetic core curing agent and preparation method thereof

    CN117924882A

  • Iron-based amorphous / nanocrystalline soft magnetic powder as well as preparation method and application thereof

    CN117954189A

Cited By

  • Preparation method of T-Core inductor based on hot pressing sintering and T-Core inductor

    CN120656842A

  • Inorganic insulation integrally-formed power inductor and preparation method thereof

    CN120690589A